2015
DOI: 10.1097/md.0000000000001189
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Hepatocellular Neoplasm With Peliosis in Cirrhotic Liver Versus Hepatocellular Carcinoma

Abstract: Atypical hepatocellular neoplasm (AHN) is an adenoma-like hepatic tumor that even occurs in noncirrhotic liver of males (any age) or females ≥50 years old, or associates focal atypical features.In this article, 2 unusual cases diagnosed in elderly cirrhotic patients, unrelated to steroids, are presented.The first case was incidentally diagnosed in an 83-year-old female. During laparoscopic surgery for cholecystectomy, hemoperitoneum was installed and laparotomy was necessary to remove a 70-mm nodular encapsula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…These bloodfilled lesions can appear similar to hemangiomas on imaging, although hemangiomas highly over-express CD34, which is a marker for reticulin and fibrous tissue. [16][17][18] CD34 positivity is also noted in normal liver tissue. This patient's pathology is not consistent with hemangioma ( Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…These bloodfilled lesions can appear similar to hemangiomas on imaging, although hemangiomas highly over-express CD34, which is a marker for reticulin and fibrous tissue. [16][17][18] CD34 positivity is also noted in normal liver tissue. This patient's pathology is not consistent with hemangioma ( Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Because of the limited amount of specimens of hepatocellular adenomas, [26] the diagnosis efficiency of 3-miRNA panel among HCC and adenomas did not evaluated in this study. Additionally, some studies have reported that miRNAs have great potential as biomarkers for the diagnosis of cholangiocarcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…[13] However, it may be difficult to distinguish between HCC and atypical hepatocellular neoplasm with peliosis in cirrhotic liver. [14] Peliosis hepatis is a rare tumor-like lesion that composed of multiple blood-filled cavities that are difficult to distinguish from other hepatic lesions unless examined by biopsy. [15,16] Imaging characteristic of peliosis hepatis is arterial enhancement without rapid washout, [16] which may be similar to type II (plateau pattern) time-concentration curve in QDSA.…”
Section: Discussionmentioning
confidence: 99%